2019
DOI: 10.1002/app.48618
|View full text |Cite
|
Sign up to set email alerts
|

Comparison in composite performance after thermooxidative aging of injection molded polyamide 6 with glass fiber, talc, and a sustainable biocarbon filler

Abstract: Degradation is an unavoidable part of a material's life making it important to both monitor and control the aging behavior of plastics. This study compares thermooxidative degraded composites of a novel bio-based and sustainable filler, Biocarbon (MBc), against that of traditional and commercially available fillers (glass fiber and talc) used in the automotive industry. The influence of thermooxidative degradation on the composites was studied under accelerated heat aging for 1000 h at 140 C. The mechanical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 44 publications
(72 reference statements)
0
11
0
Order By: Relevance
“…These data analysis showed that as AF concentration increased, the intensity of the two peaks also rose, which suggested that agave fiber induces the formation of α crystals of Ny6, as is shown by XRD. The addition of agave fiber in Ny6 improved the crystallinity degree (% X c) up to 22.4% for Ny6‐AF 20% (Table 3), which is likely attributed to chain restriction motions as explained by Jubinville et al 54 for fiber‐shaped loads‐reinforced polyamide 6 composites. The discrepancy of the % X c value for Ny6‐AF composite with 15 wt% of AF is attributed to a low dispersion of the fiber into the matrix during the melt mixing process, resulting in areas with low amounts of fiber.…”
Section: Resultsmentioning
confidence: 74%
“…These data analysis showed that as AF concentration increased, the intensity of the two peaks also rose, which suggested that agave fiber induces the formation of α crystals of Ny6, as is shown by XRD. The addition of agave fiber in Ny6 improved the crystallinity degree (% X c) up to 22.4% for Ny6‐AF 20% (Table 3), which is likely attributed to chain restriction motions as explained by Jubinville et al 54 for fiber‐shaped loads‐reinforced polyamide 6 composites. The discrepancy of the % X c value for Ny6‐AF composite with 15 wt% of AF is attributed to a low dispersion of the fiber into the matrix during the melt mixing process, resulting in areas with low amounts of fiber.…”
Section: Resultsmentioning
confidence: 74%
“…Jubinville et al also found that different additives have a nucleation effect on PA6. [ 29 ] Within the range of aging time, we can find that X c and T m increase slightly under the low aging temperature, while those increase initially followed by a decrease under the high aging temperature. On one hand, the rise of X c and T m is due to the chemicrystallization that occurred as a result of scissor of molecular segments, which can yield mobile molecular chains in the amorphous region suitable to incorporate into pre‐existing crystals.…”
Section: Resultsmentioning
confidence: 94%
“…However, the HDT value of injection molded pristine nylon 6 was observed in the range of 138–147 °C based on available grades. [ 32,49 ] This formulation may be suitable for printing patient specific prosthetic sockets. As the prepared prosthetics mostly used closer to environmental conditions (0–30 °C).…”
Section: Resultsmentioning
confidence: 99%